Brigatinib versus other second-generation ALK inhibitors as initial treatment of anaplastic lymphoma kinase positive non-small cell lung cancer with deep phenotyping: study protocol of the ABP trial - Petros Christopoulos; Farastuk Bozorgmehr; Lena Brückner; Inn Chung; Johannes Krisam; Marc A. Schneider; Albrecht Stenzinger; Regina Eickhoff; Daniel W. Mueller; Michael Thomas (BMC Cancer, 2021)
Abstract Background Availability of potent anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKI) has pushed the median survival of ALK+ non-smallcell lung cancer (NSCLC) patients to over five years. In particular, second-generation ALK TKI have demonstrated superiority compared to the first-generation compound crizotinib and are meanwhile standard first-line treatment. However, clinical courses of individual patients vary widely, with secondary development of drug resistance and intracranial progression remaining important problems. While these limitations highlight the need for better disease monitoring and additional therapeutic tools, molecular tumor features are increasingly recognized as crucial determinants of clinical outcome. This trial aims to optimize management of ALK+ NSCLC by analyzing the efficacy of second-generation ALK inhibitors in conjunction with deep longitudinal phenotyping across two treatment lines. Methods/design In this exploratory prospective phase II clinical trial, newly diagnosed ALK+ NSCLC patients will be randomized into two treatment arms, stratified by presence of brain metastases and ECOG performance status: brigatinib (experimental arm) vs. any other approved second-generation ALK TKI. Tumor tissue and blood samples will be collected for biomarker analysis at the beginning and throughout the study period to investigate baseline molecular tumor properties and analyze the development of acquired drug resistance. In addition, participating investigators and patients will have the possibility of fast-track molecular tumor and ctDNA profiling at the time of disease progression using state-of-the-art next-generation sequencing (NGS), in order to support decisions regarding next-line therapy. Discussion Besides supporting therapeutic decisions for enrolled patients, the ABP trial primarily aims to deepen the understanding of the underlying biology and facilitate development of a framework for individualized management of ALK+ NSCLC according to molecular features. Patients with low molecular risk and the perspective of a “chronic disease” will be distinguished from “high-risk” cases, molecular properties of which will be utilized to elaborate improved methods of non-invasive monitoring and novel preclinical models in order to advance therapeutic strategies. Trial registration Clinicaltrials.gov , NCT04318938. Registered March 182,020, https://www.clinicaltrials.gov/ct2/show/NCT04318938 Eudra-CT, 2019–001828-36. Registered September 302,019, https://www.clinicaltrialsregister.eu/ctr-search/search?query=2019-001828-36